LAPORAN KASUS: CUTANEOUS LIPOMA PADA ANJING RAS LOKAL - Prasetyo, Catur; Gorda, I Wayan; Sudisma, I Gusti Ngurah (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2025)
Cutaneous lipoma is a benign tumor of fatty tissue, whose presence is generally not dangerous but can cause discomfort or be aesthetically disturbing. The purpose of this case report is to outline how to diagnose and treat cases of cutaneous lipoma in dogs. The case presented involves an 8-month-old female local dog with predominantly black fur and white markings, which was diagnosed with a cutaneous lipoma. The chosen treatment method was surgery to remove the fatty mass from the cutaneous tissue of the caudal abdominal region. Before surgery, the dog received premedication with atropine sulfate subcutaneously, and anesthesia was administered using xylazine and ketamine intramuscularly, given separately. The operation to remove the tumor involved making incisions through the skin and subcutaneous tissue. The wound was closed using a continuous suture pattern with absorbable PGA 3.0 sutures for both the subcutaneous layer and the skin. Post-operative treatment included regular cleaning of the wound area with 0.9% NaCl, application of antibiotic powder, and oral administration of cefixime trihydrate and meloxicam for five days. A week after surgery, the dog showed signs of recovery based on physical and clinical evaluations.